Wafer‐scale epitaxial lift‐off of GaN using bandgap‐selective photoenhanced wet etching (Phys. Status Solidi B 8/2017). Issue 8 (8th August 2017) - Youtsey, Chris; McCarthy, Robert; Reddy, Rekha; Forghani, Kamran; Xie, Andy; Beam, Ed; Wang, Jingshan; Fay, Patrick; Ciarkowski, Timothy; Carlson, Eric; Guido, Louis
Abstract : A wafer‐scale epitaxial lift‐off (ELO) process for GaN materials has been demonstrated using bandgap‐selective photoenhanced wet etching of an InGaN release layer (see Youtsey et al., article no.1600774 ). This process has been used to lift off GaN layers grown on sapphire as well as native GaN substrates using a perforation technique to scale the process up to wafers of arbitrary size. Shown in the image is a 5‐micronthick GaN epitaxial film that was lifted‐off from a 4‐inch sapphire substrate using perforations on a 1‐mm pitch. The flexible, released GaN film is supported by a 20‐micron‐thick metal layer and has been folded over to reveal the nitrogen face of the GaN film. The wafer is under ultraviolet illumination, which produces yellow luminescence in the GaN material. The light emission can be seen to be uniform and defect‐free across the entire wafer. The ELO process uses conventional MOCVD growth to form a pseudomorphic InGaN release layer, which enables the growth of high‐quality GaN films on top of the release layer. The ELO process is non‐destructive and can enable cost reduction through multiple reuses of the bulk GaN or sapphire substrate after ELO.